Sleep hygine intervention for sleep quality in school-age children: a literature review - Nur Hijrah Tiala; Nining Suryaningsih; Suntin Suntin (Universitas Muhammadiyah Semarang, 2022)
Sleep hygiene therapy is a therapy that is taught to children to maintain personal hygiene before going to bed and prevent the development of sleep disorders in school-age children. Sleep problems and disorders are common in school-age children, the duration of sleep for school-age children is 9 to 11 yours. This study aims to obtain an overview of the application of sleep hygiene therapy to sleep pattern disorders in school-age children. Methods: literature review search conducted using 3 data bases, Pubmed, Google Scholar and Portal Garuda with research articles in the last 5 years in Indonesian and English related to the application of sleep pattern disorders in school-age children. Result: based on 5 research articles analiyzed, the application of sleep hygiene therapy can overcome sleep disorders in children and can overcome sleep disorders in children and can improve sleep quality for the better. Conlusion: the intervention of sleep hygiene for school sleep disorders is effective and can overcome sleep disorders in school-age children